Statins' Protective Effect For The Prevention Of Atrial Fibrillation Incidence After Coronary Artery Bypass Surgery - Putri, Sheila Dhiene; Safri, Zainal (Universitas Muhammadiyah Sumatera Utara, 2022)
Abstract: Atrial fibrillation (AF) after cardiac surgery is associated with an increased risk of complications, length of stay, and cost of care. Recent studies have demonstrated that statins have pleiotropic effects, including anti-inflammatory effects and preventing atrial fibrillation (AF). The objective of this study was to assess the efficacy of preoperative statin therapy in preventing AF after coronary artery bypass grafting (CABG). 53 patients underwent CABG in our hospital from February to August 2018. Patients were randomized into two groups to examine the effect of statins: those with atorvastatin 20 mg/day during the preoperative period (Atorvastatin group, n = 26) and those with rosuvastatin 10 mg/day (Rosuvastatin group, n = 27). The primary end-point is postoperative AF (POAF), with an overall incidence of postoperative AF of 11.3%. Postoperative AF incidence was insignificantly different between the atorvastatin and rosuvastatin groups (7.7% vs. 14.8%; p = 0,669). Our study indicated that atorvastatin had a similar protective effect to rosuvastatin in terms of post-operative AF prevention.Keywords: statin, post-operative AF